Educator’s perceptions of the impacts of school violence on Caribbean societies - Wallace, Wendell C. (African journal of criminology and justice studies, 2019)
Globally, school violence plays an ominous role in the education process as it has been widely recognized as having negative impacts. In this context, education in a violence-free environment is a challenge facing some schools, students and teachers in the Caribbean. Internationally, school violence is a relatively well researched area, however, both internationally and in the Caribbean, educator’s perceptions of the impacts of school violence is relatively understudied. This study explores educator’s perceptions of the impacts of school violence on Caribbean societies and offers an interpretive exploration of these perceptions. Self-administered questionnaires were randomly distributed to educators in Antigua and Barbuda, Barbados, Jamaica, St. Lucia, St. Vincent and the Grenadines and Trinidad and Tobago. To analyze the data, frequency distribution was used and the data converted into percentages. The results gleaned from one hundred and twenty respondents indicate that school violence has impacts at the individual, institutional and community levels.